Kulturowa tożsamość książki, red. Anna Cisło, Agnieszka Łuszpak, Wrocław: Wydawnictwo Uniwersytetu Wrocławskiego 2014, s. 300 (Acta Universitatis Wratislaviensis, No 3582) - Wojciechowski, Jacek (Biblioteka, 2015)
Recenzja